Comparison of propofol and thiopentone along with ketamine for paediatric MRI sedation - K. S., Kedareshvara; Dhorigol, M. G.; Mane, Rajesh; Gogate, Vandana (International Journal of Research in Medical Sciences, 2016)
Background: Children are very much scared to undergo magnetic resonance imaging (MRI) brain or any body part even along with their parents for about 15 to 25 minutes. We investigated the combination of Propofol Ketamine and Thiopentone Ketamine along with Glycopyrolate and Midazolam premedication to see safe and better sedation group for paediatric MRI. Methods: We investigated randomly 50 children of age three to five years prospectively. Children were pre-medicated with Glycopyrolate 0.01 mg/kg and Midazolam 0.05 mg/kg per body weight intravenously. Ketamine 1 mg/kg body weight was given just before shifting into the MRI machine. After body positioning either Propofol (PK group) or Thiopentone (TK group) 1 mg/kg body weight was given slowly. Children were monitored for electrocardiogram (ECG), arterial oxygen saturation (SpO2) and respiratory rate continuously. Oxygen supplementation was through the oxygen (O2) mask. Three parameters were studied 1) Repetition of drug 2) Respiratory distress during scan period and 3) Recovery time. Results: The pre-interventional characteristics including age, sex, weight, ASA grade, were comparable between two groups (p>0.050). Repetition in PK group was high compared to TK group (40% vs 8%; p=0.0081). Respiratory distress was comparable in both the groups (16% vs 24%; p=0.480) whereas recovery time was significantly shorter for PK group (4.62 ± 0.53 vs 9.86 vs 1.28; p<0.001). Conclusions: Thiopentone Ketamine combination results in lower repetition rate while Propofol Ketamine offers shorter recovery period. However, respiratory distress is almost similar.